Protocatechuic Acid, a Phenolic from Sansevieria roxburghiana Leaves, Suppresses Diabetic Cardiomyopathy via Stimulating Glucose Metabolism, Ameliorating Oxidative Stress, and Inhibiting Inflammation - Bhattacharjee, Niloy; Dua, Tarun K.; Khanra, Ritu; Joardar, Swarnalata; Nandy, Ashis; Saha, Achintya; De Feo, Vincenzo; Dewanjee, Saikat (Frontiers in Pharmacology, 2017)
Persistent hyperglycemia, impairment of redox status and establishment of inflammatory pathophysiology integrally play important role in the pathogenesis of diabetic cardiomyopathy (DC). Present study examined the therapeutic potential of protocatechuic acid isolated from the Sansevieria roxburghiana rhizomes against DC employing rodent model of type 2 diabetes (T2D). T2D was induced by high fat diet + a low-single dose of streptozotocin, (35 mg/kg, i.p.). T2D rats exhibited significantly (p < 0.01) high fasting blood glucose level. Alteration in serum lipid profile (p < 0.01) and increased levels of lactate dehydrogenase (p < 0.01) and creatine kinase (p < 0.01) in the sera of T2D rats revealed the occurrence of hyperlipidemia and diabetic pathophysiology. A significantly (p < 0.01) high levels of serum C-reactive protein and pro-inflammatory mediators revealed the establishment of inflammatory occurrence in T2D rats. Besides, significantly high levels of troponins in the sera revealed the establishment of cardiac dysfunction in T2D rats. However, protocatechuic acid (50 and 100 mg/kg, p.o.) treatment could significantly reverse the changes in serum biochemical parameters related to cardiac dysfunctions. Molecular mechanism studies demonstrated impairment of signaling cascade, IRS1/PI3K/Akt/AMPK/p 38/GLUT4, in glucose metabolism in the skeletal muscle of T2D rats. Significant (p < 0.01) activation of polyol pathway, enhanced production of AGEs, oxidative stress and up-regulation of inflammatory signaling cascades (PKC/NF-κB/PARP) were observed in the myocardial tissue of T2D rats. However, protocatechuic acid (50 and 100 mg/kg, p.o.) treatment could significantly (p < 0.05-0.01) stimulate glucose metabolism in skeletal muscle, regulated glycemic and lipid status, reduced the secretion of pro-inflammatory cytokines, and restored the myocardial physiology in T2D rats near to normalcy. Histological assessments were also in agreement with the above findings. In silico molecular docking study again supported the interactions of protocatechuic acid with different signaling molecules, PI3K, IRS, Akt, AMPK PKC, NF-κB and PARP, involved in glucose utilization and inflammatory pathophysiology. In silico ADME study predicted that protocatechuic acid would support the drug-likeness character. Combining all, results would suggest a possibility of protocatechuic acid to be a new therapeutic agent for DC in future.